The Role of MAPK Modules and ABA during Abiotic Stress Signaling. (August 2016) - de Zelicourt, Axel; Colcombet, Jean; Hirt, Heribert
Abstract : To respond to abiotic stresses, plants have developed specific mechanisms that allow them to rapidly perceive and respond to environmental changes. The phytohormone abscisic acid (ABA) was shown to be a pivotal regulator of abiotic stress responses in plants, triggering major changes in plant physiology. The ABA core signaling pathway largely relies on the activation of SnRK2 kinases to mediate several rapid responses, including gene regulation, stomatal closure, and plant growth modulation. Mitogen-activated protein kinases (MAPKs) have also been implicated in ABA signaling, but an entire ABA-activated MAPK module was uncovered only recently. In this review, we discuss the evidence for a role of MAPK modules in the context of different plant ABA signaling pathways. Trends: Abiotic stresses impact average yield in agriculture by more than 50% globally. Since ABA is a key regulator of abiotic stress responses, an understanding of its functioning at the molecular level is essential for plant breeding. Although the ABA core signaling pathway has been unraveled, several downstream events are still unclear. MAPKs are involved in most plant developmental stages and in response to stresses. Several members of the MAPK family were shown to be directly or indirectly activated by the ABA core signaling pathway. Recent evidence shows that the complete MAP3K17/18-MKK3-MPK1/2/7/14 module is under the control of ABA, whose members are under the transcriptional and post-translational control of the ABA core signaling pathway.